Impact of Organizational Learning on Library Personnel Productivity (Lead City International Journal of Library, Information & Communication Sciences, 2025)
Organizational learning is vital for boosting library personnel productivity in academic institutions by promoting continuous improvement and adaptation to new technologies. However, challenges like limited resources, lack of support, and resistance to change hinder effective learning programs, impacting productivity. This paper highlights the need for targeted professional development and strategic integration of organizational learning to improve library services and support academic goals. The paper used extensive literature review and practical insights of successful implementation of organizational learning as it affects the productivity of library personnel. This paper expounded the impact of organizational learning on the productivity of library personnel. It delved into some of the challenges that librarians’ may encounter when implementing organisational learning in order to enhance productivity. Furthermore, the paper examined the strategies that can be adopted to boost the productivity of librarians as a result of organisational learning. The paper reviewed some successful implementation of organisational learning on library personnels productivity. Organizational learning is crucial for enhancing library personnel's skills, efficiency, and productivity, driving the growth and sustainability of library operations. Overcoming challenges like limited funding through strategic collaboration and technology-driven training can foster continuous learning, improving service quality, job satisfaction, and competitiveness in the digital age. Library management should invest in continuous professional development by funding workshops, seminars, and e-learning platforms, while fostering a culture of learning through mentorship, peer sessions, and targeted training. Collaborating with external institutions and offering incentives like promotions and recognition can further motivate staff. These efforts ensure staff remain updated and engaged in their professional growth.